2017
DOI: 10.1111/cas.13425
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid enhances the therapeutic effects of oxaliplatin in colorectal cancer by inhibition of drug resistance

Abstract: It has been reported that ursolic acid has anti‐tumor activity and it enhances the therapeutic effect of oxaliplatin in colorectal cancer (CRC). However, the underlying mechanisms remain unknown. In the present study, the mechanisms of the enhancement of therapeutic effects through use of ursolic acid were investigated. We treated CRC cell lines HCT8 and SW480 with ursolic acid and oxaliplatin and monitored the effects on cell proliferation, apoptosis, reactive oxygen species (ROS) production and drug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Ki-67, CD31, and miR-29a (Prasad et al, 2012;Zhang et al, 2018) Withaferin-A (phytosterols) Withania somnifera (Solanaceae)…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…Ki-67, CD31, and miR-29a (Prasad et al, 2012;Zhang et al, 2018) Withaferin-A (phytosterols) Withania somnifera (Solanaceae)…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…## P < 0:01 is considered very significant; ### P < 0:001 is considered highly significant. 5 Oxidative Medicine and Cellular Longevity combination treatment of CREE and UA is found and shown to enhance the efficacy and reduce the side effects. Significant improvement in body weight, levels of serum insulin, liver glycogen, and antioxidant enzymes activity were observed with best effect in the combined treatment group rather than the single drug treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…Various recently studies reported the wide spectrum pharmacological potentials of UA. It exhibits a variety of effects including antimicrobial, anti-arthritic, and anticancer effects against variety of cancers [4,5]. Numerous bioactivities of UA have been reported, but till date no clinical work available which demonstrates beneficial effects to human health care.…”
Section: Introductionmentioning
confidence: 99%
“…Oxaliplatin, which is commonly used for treating colon carcinoma, had been reported to affect tumor cell glucose metabolism. 29,30 We next examined the effect of oxaliplatin on YY1 and GLUT3 expression. As shown in Figure 4D, oxaliplatin grossly suppressed the expression levels of both YY1 and GLUT3 in HCT116 p53null cells in a dose-dependent manner.…”
Section: Yin Yang 1 Enhances Tumor Cell Glycolysis In a P53-indepenmentioning
confidence: 99%